THE ROLE OF BRAND TRUST AS AN INTERVENING VARIABLE IN ONLINE CUSTOMER PURCHASE DECISION ANALYSIS OF BEAUTYPRODUCTS THE BODY SHOP INDONESIA IN THE CITY OF SEMARANG - Ika Kirana Jalantina, Dyah (SEAN Institute, 2022)
The purpose of this study was to analyze the influence of online customer reviews, brand image and product quality on customer purchasing decisions through brand trust as an intervening variable on consumers of The Body Shop Indonesia products. Customer purchasing decisions which are consumer buying decisions are influenced by brand trust, namely consumer confidence in The Body Shop brand's beauty products. Consumer trust in brands is the impact of online customer reviews by consumers after shopping online, brand image on The Body Shop beauty products and product quality or The Body Shop product quality. Using multiple regression method, data collection was carried out by distributing questionnaires to consumers who had purchased The Body Shop beauty products online in Semarang City and a total of 100 respondents as research samples. The results showed that the third independent variable, namely online customer reviews, brand image and product quality, had a positive and significant effect on the dependent variable, namely customer purchasing decisions either directly or through the intervening variable, namely brand trust.